THE INFLUENCE OF PHILOSOPHY ON THE DEVELOPMENT OF LANGUAGE SCIENCE - Rima Sarah (JURNAL AL-AQIDAH, 2022)
This study examines the influence of research is realized by applying a philosophy in the development of language science. The qualitative approach in this critical literature review of various relevant writings. From there, the researchers sees that philosophy through language is an object of reflection on the unique experience of human life. Science has been studied and developed along with philosophy itself and has been concerned with human life for centuries. Problems regarding the development of philosophy certainly have a significant influence on various other fields of science, including language. This subjectivity that will continue to attract the attention of philosophers of language researchers to discuss the aspects involved. The conclusion obtained from this research is that language is a medium in conveying philosophical statements to seek the truth of everything. In addition, philosophy serves to provide direction so that the linguistic theory developed by experts has relevance to the reality of human life.